2016
DOI: 10.1111/iwj.12546
|View full text |Cite
|
Sign up to set email alerts
|

Effects of pressure ulcer classification system education programme on knowledge and visual differential diagnostic ability of pressure ulcer classification and incontinence‐associated dermatitis for clinical nurses in Korea

Abstract: Lee YJ, Kim JY, Korean Association of Wound Ostomy Continence Nurses. Effects of pressure ulcer classification system education programme on knowledge and visual differential diagnostic ability of pressure ulcer classification and incontinence-associated dermatitis for clinical nurses in Korea. Int Wound J 2016; 13 (suppl. s1):26-32 AbstractThe objective of this study was to evaluate the effect of pressure ulcer classification system education on clinical nurses' knowledge and visual differential diagnostic ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
36
1
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(45 citation statements)
references
References 16 publications
4
36
1
4
Order By: Relevance
“…This study aimed to explain a realistic portrayal of nurses' current practices to prevent and manage PIs in one public hospital in Singapore. Compared with other studies, the participants' ethnicity is significantly more diverse because of Singapore's multiracial society and the tendency to hire non‐Singaporean nurses to compensate for the shortage of local nurses . Another significant aspect of the sociodemographic data lies in the relative homogeneity for nurses' years of experience working (1‐2 years) as this study hospital has only been established for 3 years.…”
Section: Discussionmentioning
confidence: 87%
“…This study aimed to explain a realistic portrayal of nurses' current practices to prevent and manage PIs in one public hospital in Singapore. Compared with other studies, the participants' ethnicity is significantly more diverse because of Singapore's multiracial society and the tendency to hire non‐Singaporean nurses to compensate for the shortage of local nurses . Another significant aspect of the sociodemographic data lies in the relative homogeneity for nurses' years of experience working (1‐2 years) as this study hospital has only been established for 3 years.…”
Section: Discussionmentioning
confidence: 87%
“…However, it has been reported that the accuracy of visual discrimination of stage 1 PIs using clinical photographs was 55% to 55.8%, and the accuracy increased to 74% to 74.1% after the nurses received training . It has been suggested that there is a limit to visual discrimination in correctly diagnosing the stage of PI in clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…However, it has been reported that the accuracy of visual discrimination of stage 1 PIs using clinical photographs was 55% to 55.8%, and the accuracy increased to 74% to 74.1% after the nurses received training. 13,14 It has been suggested that there is a limit to visual discrimination in correctly diagnosing the stage of PI in clinical practice. The early detection of stage 1 PIs is a predictive factor for assessing the effect of preventive interventions and preventing the PIs from becoming severe; thus, early detection could reduce the prevalence of PIs.…”
Section: Introductionmentioning
confidence: 99%
“…Tendo em conta que, a pele é uma variá-vel sensível aos cuidados de enfermagem, patente no Resumo Mínimo de Dados (9) , o objetivo da presente revisão sistemática da literatura visa identificar quais as intervenções de enfermagem que promovem a prevenção e cicatrização da DAI. (11) . Deste modo, para uma segura e consistente aplicação nos contextos clínicos, foram englobados maioritariamente níveis de evidência considerados de elevada qualidade, ou seja, até 2a, discriminados na tabela 1.…”
Section: Introductionunclassified